Nest-to-Surf Mortality of Loggerhead Sea Turtle (Caretta caretta) Hatchlings on Florida’s East Coast - Erb, Victoria; Wyneken, Jeanette (Frontiers in Marine Science, 2019)
Sea turtles are vulnerable immediately after emerging from nests and before they reach the surf. Mortality rates during this brief period are largely unknown. Many sea turtle monitoring programs measure hatchling production from nest inventories. These inventories rarely account for post-emergence mortality, leaving an unknown bias in hatchling production estimates. This study addresses the nest-to-surf data gap for Florida’s east coast nesting assemblages of loggerhead sea turtles (Caretta caretta). Five locations were surveyed during the 2016-nesting season. Across all beaches, 7.6% of the observed hatchlings did not survive to reach the water. Mortality sources varied by location. Observed predators include: mammals, birds, and crabs. Hatchling disorientation and misorientation due to photopollution occurred more frequently in urban areas than natural areas. Factors identified as important in hatchling mortality included numbers of hatchlings emerging, nest-to-surf distance, and level of urbanization. The results of this study may help sea turtle nesting managers address nest-to-surf mortality and improve hatchling production estimates.